AN ANALYSIS OF THE ENGLISH TEXTBOOK “HELLO JAKARTA GRADE V” FOR ELEMENTARY STUDENTS - Gracia Octora; Iwan Ridwan; Kelik Wachyudi (PROJECT (Professional Journal of English Education), 2023)
Learning English in elementary schools, it is essential to use textbooks suitable for students because textbooks can support the teaching and learning process in a class by studying the material. Textbooks are ideal for students and can be adapted to Permendikbud No. 8 of the 2016 framework concerning National Education Book Standards used by Education Units. This study aims to describe and analyze the feasibility of an English textbook for grade 5 elementary schools entitled "Hello Jakarta Grade 5" using the analytical framework of the National Education Standards Agency. This study uses a qualitative approach by analyzing the feasibility of the content of textbooks, starting from the aspects of the material, language, presentation of material, graphics, and components in these aspects by the National Education Standards Agency. According to the National Education Standards Agency, the analysis results show that the book "Hello Jakarta Grade 5" already meets the four criteria for a proper and appropriate book to be used in class as teaching material.